Severidades Ocupacionais associadas à inatividade física no lazer em trabalhadores - Papini, Camila Bosquiero [UNESP]; Nakamura, Priscila Missaki [UNESP]; Martins, Caroline de Oliveira; Kokubun, Eduardo [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2010)
The aim of this study was to verify associations between occupational severities and leisure time physical inactivity level in workers. Two-hundred workers of Rio Claro County participated in this study. The leisure time physical activity (active or inactive) and some occupational severities were evaluated. The statistic analyses showed that working day, overtime work and occupational intensity had not been associated with leisure time physical inactivity in workers. Only the willingness at the end of the working day had been associated to the leisure time physical inactivity; showing that workers who leave their work with some willingness have more possibilities to be active in leisure time.

O objetivo do estudo foi verificar associações entre severidades ocupacionais e nível de atividade física no lazer em trabalhadores. Para isso participaram do estudo 200 trabalhadores (71 homens e 129 mulheres) do Município de Rio Claro e região. Foram avaliados o nível de atividade física no lazer (ativo ou inativo) e algumas severidades ocupacionais. A análise estatística revelou que o tempo da jornada diária de trabalho, realização de horas extra e intensidade do trabalho não foram associados à inatividade física no lazer em trabalhadores. Somente a disposição no fim da jornada de trabalho foi associada à inatividade física no lazer, mostrando que trabalhadores que tem alguma disposição depois do trabalho são mais ativos no tempo de lazer.
Occupational severities associated to leisure time physical inactivity level in workers
Keywords: Workers; Physical activity level; Occupational severities